SELF-ACCESS CENTER AND STUDENTS’ ATTITUDE ON BEING AUTONOMOUS LEARNERS IN ENGLISH LANGUAGE LEARNING - Sulindra, Eric; Dasuki, Febe Yeni (Akademi Sekretari Widya Mandala, 2017)
The recent student-centered learning trend in language education has put more emphasis on students’ independent English Language Learning as well as more responsibility towards their success in the learning process. However, some teachers still believe that teachers should control most learning process due to the learning success. As supporting resource to English Language Learning, Self-Access Center has been admitted to be significant in language learning success. This study aimed to find out how Self-Access Center facilities were able to influence students’ attitude towards autonomy in learning. The research was descriptive qualitative. The data collection was conducted by triangulating the three instruments: questionnaires, in-depth semi structured interview and student-attendance-record. This study took place in Widya Mandala Secretarial Academy Surabaya, Indonesia, in its Self-Access Center facility. The findings were to show the students’ perception on Self-Access Center as a determining factor in their learning success, and how the center itself affected their attitude towards autonomy in learning.